2018
DOI: 10.3389/fphar.2018.01016
|View full text |Cite|
|
Sign up to set email alerts
|

Ulinastatin Inhibits Osteoclastogenesis and Suppresses Ovariectomy-Induced Bone Loss by Downregulating uPAR

Abstract: Recent studies indicate that uPAR acts a crucial part in cell migration and the modulation of bone homeostasis. As a natural serine protease inhibitor, ulinastatin owns the capacity to reduce proinflammatory factors, downregulate the activation of NF-κB and mitogen-activated protein kinases (MAPKs) signaling pathways. Osteoclastogenesis has been demonstrated to be related with low-grade inflammation which involves cell migration, thus we speculate that ulinastatin may have a certain kind of impact on uPAR so a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…36 A recent study demonstrated that uPAR expression increases during osteoclast formation, and knockdown of the gene encoding for uPAR completely inhibits the formation of osteoclasts. 37 Therefore, in this study, we evaluated the potential additive benefit of . The total number of osteoclasts was counted, and the bar graph on the right panel represents the mean ± SEM of osteoclasts counted from three animals per group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 A recent study demonstrated that uPAR expression increases during osteoclast formation, and knockdown of the gene encoding for uPAR completely inhibits the formation of osteoclasts. 37 Therefore, in this study, we evaluated the potential additive benefit of . The total number of osteoclasts was counted, and the bar graph on the right panel represents the mean ± SEM of osteoclasts counted from three animals per group.…”
Section: Discussionmentioning
confidence: 99%
“…5a to demonstrate that decreased osteolysis following these treatments has a net increase in bone volume. Since uPAR is also involved in osteoclast formation, 37 the addition of huATN-658 in the combination cohort further inhibits osteoclastogenesis. Moreover, the RNA-Seq results showed that the huATN-658 + Zometa combination treatment significantly increases the expression of COL1A2 and SPOCK3 genes encoding for type 1 collagen and osteonectin proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Cell Counting Kit‐8 (CCK‐8) assay was carried out as described previously (J. Guo et al, 2017; Huang et al, 2018). VR‐EPCs were seeded in 96‐well plates (1 × 10 4 cells/well), 24 hr later, the adherent cells were cultured with M199 medium containing different concentrations of C3k (0.1, 0.3, 0.5, and 1 μM) or DASA‐58 (1, 10, 30, and 50 μM) for 4 days.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative real‐time reverse transcription‐polymerase chain reaction (qRT‐PCR) was performed as described before (J. Guo et al, 2017; Huang et al, 2018). VR‐EPCs were plated into 6‐well plates (1 × 10 5 cells/well) and then cultured with M199 medium containing DASA‐58 (30 μM) or C3k (0.3 μM) or only DMSO for 2 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation